2022
DOI: 10.1155/2022/6190333
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Metabolite Markers Associated with Kidney Function

Abstract: Background. Chronic kidney disease (CKD) is a global public health problem. Identifying new biomarkers that can be used to calculate the glomerular filtration rate (GFR) would greatly improve the diagnosis and understanding of CKD at the molecular level. A metabolomics study of blood samples derived from patients with widely divergent glomerular filtration rates could potentially discover small molecule metabolites associated with varying kidney function. Methods. Using ultrahigh-performance liquid chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…In this study, we found that in pyrimidine metabolism and histidine metabolism (Figures 4B,C), orotidine-5P, pseudouridine, 3-Ureidopropionate, urea, 1-Methyl-L-histidine, Hydantoin-5-propionate, N-Formimino-Lglutamate and imidazole lactate rise as mGFR decreases. Consistent with previously reported results, pseudouridine is extremely correlated with mGFR and might be an ideal biomarker for CKD (Peng et al, 2022). Urea is an endogenous marker in CKD (Weiner et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that in pyrimidine metabolism and histidine metabolism (Figures 4B,C), orotidine-5P, pseudouridine, 3-Ureidopropionate, urea, 1-Methyl-L-histidine, Hydantoin-5-propionate, N-Formimino-Lglutamate and imidazole lactate rise as mGFR decreases. Consistent with previously reported results, pseudouridine is extremely correlated with mGFR and might be an ideal biomarker for CKD (Peng et al, 2022). Urea is an endogenous marker in CKD (Weiner et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…28 N6-carbamoylthreonyladenosine was associated with increased all HF risk in the fully adjusted model. It was previously associated with eGFR, 29 which could explain the slight increase in HR in our model 2. But such increase was not observed in HFpEF subtype analysis, suggesting N6-carbamoylthreonyladenosine might have a different effect on patients with HFpEF than other HF types.…”
Section: Metabolic Signatures Of Hf Hfpef and Hfrefsupporting
confidence: 50%
“…Consistent with our finding, it has been reported that N6-carbamoylthreonyladenosine was significantly associated with systolic blood pressure ( 41 ). It has been identified as a biomarker for chronic kidney disease progression in children ( 50 , 51 ) and highly correlated with glomerular filtration rate ( 52 ). Hypertension can often lead to end organ damage including renal dysfunction and chronic kidney disease ( 53 ).…”
Section: Discussionmentioning
confidence: 99%